2019
DOI: 10.31234/osf.io/a967b
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Identity Commitments in Depressive Symptoms and Stressful Life Events in Adolescence and Young Adulthood

Abstract: The formation of a stable identity, consisting of a strong set of commitments, is a key developmental task in adolescence and young adulthood. Not resolving this task and lacking strong identity commitments is related to difficulties like depressive symptoms and stressful life events. However, the exact role of identity commitments in these negative experiences has remained unclear. In two longitudinal studies in the Netherlands spanning eight and six years, respectively, we examined the associations between c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Contrary to our expectation, we did not find evidence that the experience of a stressful event is related to change in identity (Tables 4 and 5). As such, our findings are partially consistent with an earlier study which revealed that stressful events were related to occupational, but not relational commitment, in adolescence (Van Doeselaar et al, 2018). However, our findings are inconsistent with studies on stressful events and identity in adulthood, which revealed decreases in commitment and increases in exploration and reconsideration within individuals following the occurrence of an event (e.g., Anthis, 2002).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Contrary to our expectation, we did not find evidence that the experience of a stressful event is related to change in identity (Tables 4 and 5). As such, our findings are partially consistent with an earlier study which revealed that stressful events were related to occupational, but not relational commitment, in adolescence (Van Doeselaar et al, 2018). However, our findings are inconsistent with studies on stressful events and identity in adulthood, which revealed decreases in commitment and increases in exploration and reconsideration within individuals following the occurrence of an event (e.g., Anthis, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, although we found no support for a relation between stressful life events and identity (Tables 4 and 5), both our t ‐tests (Tables 1 and 2) and LCS models (footnote 1) evidenced a link of low educational commitment and high educational reconsideration to the educational event. This is in line with work by Van Doeselaar et al (2018), which found that occupational commitment was related to the experience of fewer events. This suggests that in the case of life events which may, in part, be triggered by the individual (e.g., repeating a grade), identity could be a predictor rather than a consequence.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Unresolved existential conflicts-or those inadequately defended-constitute threats to identity and are associated with both depressive and suicidal symptomatology. 3 Like other stress states, existential conflicts are not intrinsically pathological-they invoke the need for specific types of mastery, which, in the logotherapy tradition, is fostered by social connectedness and a sense of purpose. 4,5 Logotherapy seeks to meld elements contemporarily associated with positive psychology-goal-setting, hope, selfefficacy, engagement in life-with the serious deliberation of existential questions and use of one's capacity for freedom of will.…”
mentioning
confidence: 99%